Maternal gut microbiota in the health of mothers and offspring: from the perspective of immunology - Lu, Xiaowen; Shi, Zhan; Jiang, Lingling; Zhang, Songying (Frontiers in Immunology, 2024)
Due to the physiological alteration during pregnancy, maternal gut microbiota changes following the metabolic processes. Recent studies have revealed that maternal gut microbiota is closely associated with the immune microenvironment in utero during pregnancy and plays a vital role in specific pregnancy complications, including preeclampsia, gestational diabetes, preterm birth and recurrent miscarriages. Some other evidence has also shown that aberrant maternal gut microbiota increases the risk of various diseases in the offspring, such as allergic and neurodevelopmental disorders, through the immune alignment between mother and fetus and the possible intrauterine microbiota. Probiotics and the high-fiber diet are effective inventions to prevent mothers and fetuses from diseases. In this review, we summarize the role of maternal gut microbiota in the development of pregnancy complications and the health condition of future generations from the perspective of immunology, which may provide new therapeutic strategies for the health management of mothers and offspring.